2006
DOI: 10.1021/bi061871+
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Affects the Stability, Hydration, and Packing of Protofibrils and Fibrils of the Wild Type and Variants of α-Synuclein

Abstract: Parkinson's disease (PD) is characterized by the presence of cytoplasmic inclusions composed of R-synuclein (R-syn) in dopaminergic neurons. This suggests a pivotal role of dopamine (DA) on PD development. Here, we show that DA modulates differently the stability of protofibrils (PF) and fibrils (F) composed of wild type or variants of R-syn (A30P and A53T) as probed by high hydrostatic pressure (HHP). While in the absence of DA, all R-syn PF exhibited identical stability, in its presence, the variantcomposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 43 publications
1
46
0
3
Order By: Relevance
“…1D). Although it has been suggested that DA specifically stabilizes aS oligomers, the presence of fibrils can be observed after long term incubation with DA (30). This misleading conclusion might be attributed to the fact that the effect of DA oxidation products on ThT fluorescence has been neglected.…”
Section: Methodsmentioning
confidence: 99%
“…1D). Although it has been suggested that DA specifically stabilizes aS oligomers, the presence of fibrils can be observed after long term incubation with DA (30). This misleading conclusion might be attributed to the fact that the effect of DA oxidation products on ThT fluorescence has been neglected.…”
Section: Methodsmentioning
confidence: 99%
“…The image reveals the ribbon structure with a width 8.7±2.7nm and 25±5nm and height 4.5±1.3nm. The cross section of the smaller width fiber seems to follow Gaussian distribution while cross section of the larger width fiber is square, with a little bump in the center [48] of the fiber. This implied that the fiber that has smaller width have one unit while the wider fibers originated from two fibers running parallel to each other.…”
Section: High Resolution Image Reveals Blob-like Nanoribbonmentioning
confidence: 93%
“…64 Follmer e colaboradores mostraram que DA interage com a-sinucleína e modula diferentemente a estabilidade de agregados gerados a partir das formas selvagem ou mutantes da proteína. 65 Na ausência de DA, protofibras de a-sinucleína exibem estabilidades semelhantes quando submetidas à dissociação por pressão hidrostática. Entretanto, protofibras geradas a partir das variantes da a-sinucleína (Ala30Pro ou Ala53Thr), quando em presença de DA, apresentaram uma maior estabilidade quando comparadas às protofibras geradas a partir da forma selvagem da proteína.…”
Section: Figura 3 Hipótese Termodinâmica Para O Enovelamento Proteicunclassified
“…66 Visto que selegilina previne (ou retarda) o processo de oxidação da DA, uma importante questão é de que forma este fármaco influenciaria no sistema a-sinucleína-DA, quando estes dois fármacos são combinados na terapia da DP. Diante dos dados mostrando o efeito da DA sobre a agregação da a-sinucleína previamente discutidos, 65 uma abordagem de tratamento racional para DP deverá considerar a ação combinada destes fármacos na doença.…”
Section: Figura 3 Hipótese Termodinâmica Para O Enovelamento Proteicunclassified
See 1 more Smart Citation